2D electrostatic PIC algorithm for laser induced studying plasma in vacuum. (February 2016) - Álvarez, C A.; Riascos, H; Gonzalez, C
Abstract: Particle-In-Cell(PIC) method is widely used for simulating plasma kinetic models. A 2D-PIC electrostatic algorithm is implemented for simulating the expansion of a laser- induced plasma plume. For potential and Electric Field calculation, Dirichlet and periodic boundary conditions are used in the X (perpendicular to the ablated material) and Y directions, respectively. Poisson-solver employs FFTW3 library and the five-point Laplacian to compute the electric potential. Electric field calculation is made by central finite differences method. Leap-frog scheme updates particle positions and velocities at each iteration. Plume expansion anlysis is done for the Emission and Post-Emission stages. In the Emission phase (while the laser is turned on), fast electron expansion is observed and ion particles remain near the surface of the ablated material. In the post-emission stage (with the laser turned off) the charge separation produces an electric field that accelerates the ions leading to the formation of a KeV per particle Ion-Front. At the end of the expansion, fastest electrons escape from the simulation space; an almost homogeneous ion-electron distribution is observed, decreasing the electric field value and the Coulomb interactions.